Directional noncovalent interactions: Repulsion and dispersion - Elkerdawy, Ahmed; Murray, Jane S.; Politzer, Peter; Bleiziffer, Patrick; Heßelmann, Andreas; Görling, Andreas; Clark, Timothy (Journal of Chemical Theory and Computation, 2013)
The interaction energies between an argon atom and the dihalogens Br , BrCl, and BrF have been investigated using frozen core CCSD(T)(fc)/aug-cc-pVQZ calculations as reference values for other levels of theory. The potential-energy hypersurfaces show two types of minima: (1) collinear with the dihalogen bond and (2) in a bridging position. The former represent the most stable minima for these systems, and their binding energies decrease in the order Br > Cl > F. Isotropic atom-atom potentials cannot reproduce this binding pattern. Of the other levels of theory, CCSD(T)(fc)/aug-cc-pVTZ reproduces the reference data very well, as does MP2(fc)/aug-cc-pVDZ, which performs better than MP2 with the larger basis sets (aug-cc-pVQZ and aug-cc-pvTZ). B3LYP-D3 and M06-2X reproduce the binding patterns moderately well despite the former using an isotropic dispersion potential correction. B3LYP-D3(bj) performs even better. The success of the B3LYP-D3 methods is because polar flattening of the halogens allows the argon atom to approach more closely in the direction collinear with the bond, so that the sum of dispersion potential and repulsion is still negative at shorter distances than normally possible and the minimum is deeper at the van der Waals distance. Core polarization functions in the basis set and including the core orbitals in the CCSD(T)(full) calculations lead to a uniform decrease of approximately 20% in the magnitudes of the calculated interaction energies. The EXXRPA+@EXX (exact exchange random phase approximation) orbital-dependent density functional also gives interaction energies that correlate well with the highest level of theory but are approximately 10% low. The newly developed EXXRPA+@dRPA functional represents a systematic improvement on EXXRPA+@EXX. © 2013 American Chemical Society.